2013
DOI: 10.1111/rda.12203
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Regression in Bovine Corpora Lutea: Regulation by Local Survival and Death Pathways

Abstract: ContentsThe bovine corpus luteum (CL) is a transient gland with a life span of only 18 days in the cyclic cow. Mechanisms controlling CL development and secretory function may involve factors produced both within and outside this gland. Although luteinizing hormone (LH) surge is the main trigger of ovulation and granulosa cells luteinization, many locally produced agents such as arachidonic acid (AA) metabolites, growth factors and cytokines were shown to complement gonadotropins action in the process of CL de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 137 publications
(228 reference statements)
0
43
0
Order By: Relevance
“…In the present study, PGF did not affect RIPKs mRNA expression in a pure population of cultured LSCs. Therefore, it could be concluded that the luteolytic action of PGF on bovine CL in vivo is mediated by several auto/paracrine factors which activate luteolytic mechanisms responsible for structural and functional luteal regression38. Similarly, the effect of PGF on RIPKs expression might depend on some mediators or upon cell composition and contact.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PGF did not affect RIPKs mRNA expression in a pure population of cultured LSCs. Therefore, it could be concluded that the luteolytic action of PGF on bovine CL in vivo is mediated by several auto/paracrine factors which activate luteolytic mechanisms responsible for structural and functional luteal regression38. Similarly, the effect of PGF on RIPKs expression might depend on some mediators or upon cell composition and contact.…”
Section: Discussionmentioning
confidence: 99%
“…These observations support our earlier findings (Liptak et al 2005) that activated immune cells may contribute a factor (or factors) that impair steroidogenesis in response to LH. It is known that activated monocytes produce inflammatory cytokines, nitric oxide, and reactive oxygen species (Murray & Wynn 2011, Zhou et al 2014) all of which may contribute individually or in combination to the inhibition of progesterone synthesis (Al-Gubory et al 2012, Quirk et al 2013, Skarzynski et al 2013). In the in vivo setting, activated monocytes may also secrete matrix metalloproteinases that contribute to the degradation of the extracellular matrix (Murray & Wynn 2011), which could facilitate the recruitment of additional inflammatory cells to the regressing corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…Structural luteolysis (destruction and removal of the luteal cells) is also required to keep the ovary in proper proportion to the rest of the reproductive tract (Skarzynski et al, 2013). Luteolysis is defined as the loss of function and subsequent involution of the luteal structure.…”
Section: Discussionmentioning
confidence: 99%